Respuesta :

Answer:

[tex]{x}^{2} + {y}^{2} + 12y + 20 = 0[/tex]

[tex]{x }^{2} + {(y + 6)}^{2} = 16 [/tex]

Step-by-step explanation:

The equation of a circle with center (a,b) and radius r, is given by:

[tex] {(x - a)}^{2} + {(y - b)}^{2} = {r}^{2} [/tex]

The given circle has centre (0,-6) and radius r=4.

We substitute these values into the formula to get:

[tex]{(x - 0)}^{2} + {(y - - 6)}^{2} = {4}^{2} [/tex]

This implies that:

[tex]{x }^{2} + {(y + 6)}^{2} = 16 [/tex]

When we expand, we get:

[tex]{x}^{2} + {y}^{2} + 12y + 36 = 16[/tex]

The general form is :

[tex]{x}^{2} + {y}^{2} + 12y + 20 = 0[/tex]